LITERASI GIZI ANAK PERKOTAAN MELALUI PERMAINAN EDUKASI GO-ZI (GO-BERGIZI) - Syaiful, Yuanita; Wahyudi, Agus; Pramiasti, Hana Dodik (PPM STIKES Adi Husada, 2024)
Introduction & Aim: A School-age children need healthy nutrition or food to support their growth and development. Food provides energy and nutritional intake for school-age children. The reality at the activity location is that only 5 out of 50 students in grades I, II and III have breakfast and bring lunch to school. In reality, snacks or food available in the school environment are most in demand by school-age children. School children do not yet know the healthy food needed by the body. Snacks at school do not contain enough nutrition to meet the body's needs. For this reason, it is necessary to educate healthy snacks to gain knowledge about healthy snacks. The increasing problem of elementary school children's nutrition in urban areas, the Community Service (PKM) team collaborated with partners, namely the ISCO Foundation Simokerto Work Unit to conduct elementary school children's nutritional literacy through educational games. The purpose of this activity is to increase the knowledge of school-age children to consume healthy foods. Method of Activity: The implementation method used is the joyful learning concept starting with an initial lecture, discussion and practice of making healthy food in the form of fruit salad. Results: The results of the implementation of the activity are that school-age children are very enthusiastic and interactive in participating in the activity and there is an increase in knowledge is good 88% (22 respondents), positive attitudes is 96% (24 respondents) and actions is 84% (21 respondents) in choosing healthy nutritious snacks. Discussion: this activity is able to provide knowledge, attitudes and actions about healthy snacks and change the behavior of school-age children from an early age to choose and consume healthy snacks and foods.